Stock portfolio optimization with cryptocurrency diversification - Bujnošek, Tomáš (2022)
The objective of this master's thesis is to help stock investors, which are often reluctant or even scared to buy any cryptocurrency, by composing sets of portfolios, which would mathematically backed the intention to invest in this phenomenon and consequently help diversify the stock portfolio. In the first chapter, cryptocurrencies are briefly introduced, along with their progression until the present and their pitfalls, as well as means of trading. Then we take a look at stocks and their two main local markets --- Prague Stock Exchange and RM-SYSTÉM. Before the main empirical analysis part of the thesis, we defined statistical elements and models used in the portfolio optimization, which are used later on. Mean-Variance, Mean-CVaR and Mean-Semivariance are explained in detail. The most extensive and imperative chapter of this master's thesis is the empirical analysis, where stocks traded on RM-SYSTÉM were analysed and portfolios were created, purely consisting of stocks as well as including cryptocurrencies. Results are compared across the models and recommended portfolios are listed. Efficient frontiers of all models were very similar, however the compositions of investment portfolios were often distinctly different. From the results, portfolios from Mean-Semivariance model seemed as the best choice. Investors can choose from a range of listed portfolios, if they consider investing in stocks too. As the models suggested, already existing stock portfolios can also be enhanced by cryptocurrencies.